Out of the closet, into the open: professionalism, power and the personal in development. (12th October 2007) - Chambers, Robert
In development thinking and practice, normal professionalism, power and personal orientations are linked with a paradigm associated with things. Paradigm here refers to mutually reinforcing concepts, values, methods, behaviours, relationships and mindsets. A shift of balance is needed to a paradigm associated with people. The realities experienced by poor and marginalised people differ from those projected by professionals. Many errors and failures have resulted. An agenda for action includes redefinition of what is good science, reversing power relations, a pedagogy for the powerful, transforming tertiary education, and critical personal reflection.